INVESTIGATION PHYLOGENETIC RELATIONSHIPS MAJOR GENOTYPES MYCOBACTERIUM TUBERCULOSIS BY MIRU-VNTR-24 GENOTYPING - A. A. Lats; O. B. Ogarkov; S. N. Zhdanova; A. N. Zarbuev; L. S. Untanova; M. V. Badleeva; B. D. Zanaeva; O. Ts. Tsydypova (Acta Biomedica Scientifica, 2013)
Thirty-one isolates of M. tuberculosis was identified in Buryatia by MIRU-VNTR-24 typing and deletion analysis by RD105 and RD207. Beijing family strains accountedfor 67,4 % and had a variety of profiles with a prevalence (22,6 %) of two modern epidemic subtype Beijing MIT17 and MIT16. Strains Beijing MIT 642 differed in the number of repeats of the variable loci, it may reflect a longer circulation of these subtypes without shaping their properties of epidemic circulating strains in modern populations, or they had epidemic importance in the past. It is also apparent heterogeneity in the number of loci among strains according to group LAM, T, and X, which requires additional research. The aim of this work was to determine the current epidemiologically important genotypes of Mycobacterium tuberculosis, as well as the genotypes had an epidemic importance in the past as an example of the region with a high prevalence of tuberculosis - the Republic of Buryatia.